Old Nordic and Christian elements in Saami ideas about the realm of the dead - Pettersson, Olof (Scripta Instituti Donneriani Aboensis, 1987)
The fact that a word or concept has been borrowed from outside does not mean that the original content, the original ideas which the loan word in question expresses, have also been adopted. This is by no means the case when it is a question of abstract words and notions, such as the afterlife. A word, an idea, a custom is taken over but filled with new content; in its new context it acquires a genuinely Saami conceptual load, which has its original domiciliary rights in Saami, north Eurasian culture. The present brief notes on the Nordic and Christian influence on Saami ideas about the realm of the dead proceed from the Saami religion as a whole, examining and explaining it from an external perspective: what connecting-points are there in the "original" mother tradition for the new ideas which have been adopted over the course of time and which have been grafted on to the old? The first and fundamental starting-point for the study of the meeting of the Saami religion with the old Nordic and Christian ones will be the Saami religion itself in its Finno-Ugric and North Euroasiancontext and not the old Norse or Christian beliefs. The question is what has inspired ideas: Are they ideas which have emerged from the Saamis' own religion, or are these ideas the result of old Norse/Christian influence? As far as old Norse influence is concerned, its relevance seems to be limited to the saivo concept. The sources for Saami religion which we possess are not primary sources, which go back to the Lapps themselves; they have been assembled by outsiders. Those who compiled these records were "children of their time" and bound by the conceptual models of the day and by the frames of reference of their religion—Christianity. The Saami realm of death, Jabmeaimo, is Saami in character, with certain Christian elements (purgatory, heaven–hell, heavenly god–devil).